Intestinal parasites in paper money circulating in the city of Diamantina (Minas Gerais, Brazil) - Costa MA (Research and Reports in Tropical Medicine, 2018)
Marina A Costa,1 Layane M Teodoro,1 Gustavo H Bahia-de-Oliveira,2 Ana Paula N Nunes,3 Ricardo A Barata1 1Laboratório de Parasitologia, Departamento de Ciências Biológicas, Universidade Federal dos Vales dos Jequitinhonha e Mucuri, Diamantina, MG, Brazil; 2Laboratório de Doenças Parasitárias, Departamento de Farmácia, Universidade Federal dos Vales dos Jequitinhonha e Mucuri, Diamantina, MG, Brazil; 3Laboratório de Bioestatística e Epidemiologia, Departamento de Ciências Básicas, Universidade Federal dos Vales dos Jequitinhonha e Mucuri, Diamantina, MG, Brazil Background: Banknotes are objects of great turnover and diffusion among the population, and can be efficient mechanisms in the dissemination of several intestinal parasites. This study investigated the presence of biological forms of intestinal parasites present in circulating cash banknotes in the city of Diamantina, Minas Gerais, Brazil, aiming to propose interventions aimed at improving local public health. Materials and methods: Between February and April 2017, samples of banknotes collected in five commercial establishments of the city were analyzed, namely: 1) gas station, 2) supermarket, 3) butchery, 4) pharmacy and 5) free fair. Ten circulating banknotes of each value (R$2.00, R$5.00, R$10.00, R$20.00, R$50.00 and R$100.00) were exchanged for new banknotes, washed with Tween 80 and, after spontaneous sedimentation, analyzed under an optical microscope with a magnification of 10× and 40×. Results: Cysts of Entamoeba coli (74.60%), cysts of Endolimax nana (16.94%), Giardia lamblia cysts (4.44%), unidentified nematode larvae (2.02%), Hymenolepis sp. (0.81%), Taenia sp. (0.81%) and Ancylostomidae larvae (0.40%) were found. Conclusions: The results revealed the need for improvements in basic sanitation, health and education activities that emphasized the importance of proper hand hygiene. Keywords: intestinal parasites, banknotes, Diamantina